Inuit perspectives on sustaining bilingualism in Nunavut - Tulloch, Shelley; Pilakapsi, Quluaq; Shouldice, Monica; Crockatt, Kim; Chenier, Cayla; Onalik, Janet (Études/Inuit/Studies, 2009)
This article presents an Inuit perspective on how bilingualism and biliteracy may be achieved and sustained in Nunavut. The Nunavut Literacy Council interviewed “language role models” (i.e., Inuit who are admired for their skill in acquiring, using, and transmitting language) in order to gain their insights into language, literacy, and learning processes in their communities. Interviews show that the role models articulate language, subsistence, social, and socioeconomic skills and practices as parts of an integrated whole. Bilingualism and biliteracy are conceptualised as continua of practice, where prioritised forms of expression reflect Inuit values, and are linked to specific uses and outcomes. Role models present language learning as lifelong, holistic, modelling-based, and anchored in meaningful and safe contexts, including spaces, activities, and relationships. Their perspectives are essential for the development of non-formal educational strategies to support thriving bilingualism in Nunavut.